2021
DOI: 10.3390/app11115271
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Bioceramic Bone Graft with Platelet-Rich Plasma for Rapid Bone Healing and Regeneration in a Rabbit Model

Abstract: This study aimed to investigate the effect of combining an innovative bioceramic α-calcium sulfate hemihydrate (α-CSH, CaSO4⋅0.5H2O) bone graft and platelet-rich plasma (PRP) to accelerate bone healing and regeneration in a rabbit model. The bone graft material was implanted bilaterally on rabbit’s artificially maxillary sinus defects: the right maxillary sinus received α-CSH, while α-CSH combine with PRP (α-CSH/PRP) was grafted in left site. The quantity and quality of bone formation after implantation were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Therefore, in the radiographic appearance, there was no wound closure in all treatments in the second week. In the biological process of bone repair, the final phase, namely the remodeling phase, begins with the formation of granulation tissue [42]. Histological analysis in this study showed that the bone healing process had been seen in the second week.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, in the radiographic appearance, there was no wound closure in all treatments in the second week. In the biological process of bone repair, the final phase, namely the remodeling phase, begins with the formation of granulation tissue [42]. Histological analysis in this study showed that the bone healing process had been seen in the second week.…”
Section: Discussionmentioning
confidence: 58%
“…The α-CSH, a substance with remarkable characteristics such as high self-setting strength, excellent osteoinductive properties, biocompatibility, and angiogenesis capabilities, has emerged as a popular alternative to traditional bone grafts [ 29 - 31 ]. Previous in vitro and in vivo studies conducted by our team have demonstrated the ability of α-CSH to promote angiogenesis and enhance osteogenesis [ 14 , 17 , 29 ]. Given the strategic development of α-CSH as a potential biomaterial for bone regeneration, it holds promise as a unique biocomposite bone graft material to be investigated in this study [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mRNA expression and the protein expression in P3 were higher than that in P0 at both time points, confirming that the addition of PRP had a clear osteogenic-inducing activity. Several past studies showed that the addition of PRP in human clinical trials increases BMD in maxillary sinus defects, reduces defect volume, and increases granulation, osteoblast, and angiogenesis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSH bone graft combined with autologous platelet gel was more effective than CSH alone in treating maxillary sinus defect. CSH bone graft with PRP showed an increase in bone mineral density (BMD), granulation tissue, and angiogenesis at two weeks after implantation [ 30 ].…”
Section: Introductionmentioning
confidence: 99%